Treatment of Cheese Whey and Bioelectricity Generation in MFCs as Substitute Source of Energy in Wastewater - Shetaya Bawa Gadima; Sunday Onyebuchi Ukanwa; Joshua Tunde Olaifa (Journal of Bioresources and Environmental Sciences, 2025)
Renewable energy is a primary energy source that naturally replenishes itself over time. It is derived from various large-scale sources, including ocean tides, sunlight, rainfall, wind, biomass, and geothermal heat generated deep within the Earth. In 2008, about 19% of global energy consumption came from renewable sources, with approximately 13% from biomass and 3.2% from hydroelectric power. A microbial fuel cell (MFC) is a reliable technology that generates electricity while removing contaminants from wastewater. The bacteria in the MFC's anode facilitate the breakdown of the substrate, producing electrons and protons through anaerobic respiration of the substrate. This research is based on finding a more effective means and technique for high production of electricity using MFCs as well as to ascertain the efficiency of MFCs in the treatment of Whey as a wastewater.  Methods such the APHA, photometric method, turbidometry and ascorbic acid methods were used to determine components like BOD, COD, TSS, phosphorus and sulphate contents respectively. Cheese whey shows promise for electricity generation in microbial fuel cells (MFCs) compared to other biomass sources. The highest voltage and current achieved with cheese whey were 56.8 mV and 5.68 mA, while the maximum current and power densities for MFC I were 0.339 mA/cm² and 19.2 mW/cm². In MFC II, peak voltage and current reached 73.7 mV and 7.37 mA, with a maximum current density of 0.44 mA/cm² and power density of 32.4 mW/m². This experiment showed efficient COD removal rates of 83.97% and 92.85% for MFC I and MFC II, respectively, and BOD₅ values of 61.95 and 73.95, indicating good biodegradability of the substrate, with BOD/COD ratios of 0.65 and 0.60.